Effects of induced salinity on BOD reaction kinetics of river water samples (Kesan peningkatan kemasinan terhadap kinetik tindak balas keperluan oksigen biokimia 5 hari menggunakan sampel air sungai) - Zainudin, Zaki; Mohamed, Maketab; Ramli, Mohd. Rosslim (Malaysian Society of Analytical Sciences (ANALIS), UKM, 2010)
Biochemical Oxygen Demand (BOD) is a typical parameter used in assessing organic pollution strength in surface waters and is normally tested over a 5-day period at an incubation temperature of 20°C (BOD5). The accuracy of this constituent, in assessing organic contamination under brackish conditions has always been known to be somewhat limited as elevated concentrations of chloride (Cl-) disrupts microbial activity from osmotic cellular degradation, causing the bottle decay rate, k1, to be effected. The aim of this study was to quantify the effects of induced salinity on k1, with varying levels of sodium chloride (NaCl) concentration (5 – 25 ppt), towards six mildly polluted to polluted tropical river water samples. The observed variations ranged between 0.10 – 0.25/day of k1 for the stipulated samples using the Thomas graphical method for determination of the k1 rate constant. Sg. Rawang depicted the highest quantum of difference in k1, with decrement from 0.754/day (0 ppt) to 0.513/day (25 ppt), whereas Sg. Klang showed the lowest quantum, from 0.306/day (0 ppt) to 0.265/day (25 ppt).